PENGARUH MODEL PEMBELAJARAN WORD SQUARE TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS IV DI SD NEGERI 31 BANDA ACEH - Annisa Zhafira Annisa; Nurmasyitah; Mislinawati (Jurnal Binagogik, 2025)
This study is motivated by the low level of student engagement in Pancasila Education learning at SD Negeri 31 Banda Aceh, particularly in grade IV students who still rely on the lecture method. This issue leads to inadequate understanding and suboptimal learning outcomes. Therefore, this research aims to determine the effect of the Word Square learning model on the learning outcomes of Pancasila Education in grade IV students at SD Negeri 31 Banda Aceh. This study employs a quantitative approach with a quasi-experimental design, involving two classes as samples: an experimental class using the Word Square model and a control class using the lecture method. The instruments used were pretest and posttest. Data analysis was performed using normality tests, homogeneity tests, Wilcoxon test, paired t-test, and Mann-Whitney U test. The results indicate a significant improvement in the learning outcomes of the experimental group compared to the control group, with a significance value of 0.000 in both the paired t-test and Mann-Whitney U test, meaning the Word Square model is more effective in improving students' learning outcomes. The conclusion of this study is that the implementation of the Word Square learning model can be an effective alternative to enhance student understanding and engagement in Pancasila Education learning